2016
DOI: 10.1245/s10434-015-5065-3
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Predictors of Weight Loss After Gastrectomy for Cancer

Abstract: Background Weight loss following gastrectomy for patients with gastric cancer has not been well characterized. We assessed the impact of patient and procedure-specific variables on postoperative weight loss following gastrectomy for cancer. Methods A prospectively maintained gastric cancer database identified patients undergoing gastrectomy for cancer. Clinical and pathologic characteristics, baseline body mass index (BMI), and postoperative weights were extracted. Change in weight was analyzed by percent ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
56
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 16 publications
(16 reference statements)
14
56
1
1
Order By: Relevance
“…As to long-term function, changes of serum hemoglobin and body weight after gastrectomy were reported. The present results for body weight loss and decrease in serum hemoglobin were not worse than the body weight loss (14.1 -30.0%) [32][33][34][35][36] and decrease in serum hemoglobin (9.7%) [33] at 12 months after total gastrectomy. Ahn et al [17] first reported 43 cases of DTR after LPG, and they performed a Roux-en-Y esophagojejunostomy by intracorporeal anastomosis with a circular stapler by a minilaparotomy, and side-to-side gastrojejunostomy was performed in an extracorporeal fashion using 2 linear staplers.…”
Section: Discussioncontrasting
confidence: 42%
“…As to long-term function, changes of serum hemoglobin and body weight after gastrectomy were reported. The present results for body weight loss and decrease in serum hemoglobin were not worse than the body weight loss (14.1 -30.0%) [32][33][34][35][36] and decrease in serum hemoglobin (9.7%) [33] at 12 months after total gastrectomy. Ahn et al [17] first reported 43 cases of DTR after LPG, and they performed a Roux-en-Y esophagojejunostomy by intracorporeal anastomosis with a circular stapler by a minilaparotomy, and side-to-side gastrojejunostomy was performed in an extracorporeal fashion using 2 linear staplers.…”
Section: Discussioncontrasting
confidence: 42%
“…In this study, overweight/obese patients lost an average of more than 10% of body weight after LPPG; this weight loss was similar to that after LDG. Previous studies have shown that overweight/obese patients tend to lose a higher proportion of body weight than nonoverweight/non-obese patients after standard curative resection of GC, such as distal or total gastrectomy [15,16]. The present study focused on body weight change following a function-preserving procedure, PPG, in which body weight is generally expected to be well maintained.…”
Section: Discussionmentioning
confidence: 98%
“…In an Asian series, Kong et al [15] found that overweight patients (body mass index [BMI] ≥ 25 kg/m 2 ) were likely to lose excessive body weight and to achieve ideal body weight after curative gastrectomy. In a Western series, Davis et al [16] reported that the extent of weight loss after gastrectomy for GC was associated with preoperative BMI (≥ 30 kg/m 2 versus < 30 kg/m 2 ) as well as extent of gastric resection (total versus subtotal). However, those reports were based on clinical data after standard gastrectomy for GC.…”
Section: Introductionmentioning
confidence: 99%
“…One-year post-operative BMI was the weight measured between 9 and 15 months after surgery. Post-operative BMI tends to be maintained after 12 months regardless of the type of operation [19].…”
Section: Patientsmentioning
confidence: 98%